Organizational behavior manning multi-generational perspective expectation for performance - Kithuri, Fr. Dr. Kinoti E.; Kithuri, Fr. Dr. Elias Kinoti (Meru Universty of Science and Technology International Conference (MUSTIC), 2025)
For the first time in history, there are five generations in the workplace.; Traditionalists—born 1925 to 1945, Baby Boomers—born 1946 to 1964, Generation X—born 1965 to 1980, Millennia’s—born 1981 to 2000, Generation Z—born 2001 to 2020, (preparing for (GenAlpha 2021-). The commonalities are more than the difference, but often we focus on differences that are obviously due to each generations experience and circumstance, to the detriment of health life-work relationship and workplace organizational performance. The study method utilized is systematic review of studies on differences and commonalities of the generations. Unveiling and unmasking the myths that comes with Multigenerational presence in organizations. This knowledge’s goal is forming basis for intervention that create multigenerational teams for wellbeing at work place as well as performance and success of the organization. Results indicate that there are generally four generations in modern workplace. Each of the generation carry with the characteristics that peculiar to them, as well as history with experiences different epoch events in their time and shaped their perspective, as well as their value systems both at work place and personal life. The study also unveiled multiple myths that contribute to making it difficult for multigenerational team to work together. The study recommends models of team building interventions in work place and organizations as well as in community setting for wellbeing of the organizations and staff.